Peran literasi informasi dalam meiningkatkan kualitas pemanfaatan perpustakaan digital di era 4.0 - Mufarrohah, Mufarrohah (Maliki Interdisciplinary Journal, 2025)
This article aims to analyze the role of information literacy in improving the quality of digital library utilization in the 4.0 era. Technological developments have brought significant changes in information acces, with digital libraries becoming one of the main academic resource providers. Howevwer, the main challenge faced by users is how to select, evaluate, and utilize credible information amid the flood of data. This article employs a literature riview approach by examining previous studies related tp information literacy and the use of difital libraries. The findings indicate that information literacy significantly contributes to encouraging users to be more critical of information quality, increasing the effectiveness of information retrieval, and strengthening the role of difital libraries as centers of knowledge in the digital era.